2005
DOI: 10.1063/1.2137890
|View full text |Cite
|
Sign up to set email alerts
|

Off-diagonal magnetoimpedance in field-annealed Co-based amorphous ribbons

Abstract: The off-diagonal magnetoimpedance in field-annealed CoFeSiB amorphous ribbons was measured in the low-frequency range using a pickup coil wound around the sample. The asymmetric two-peak behavior of the field dependence of the off-diagonal impedance was observed. The asymmetry is attributed to the formation of a hard magnetic crystalline phase at the ribbon surface. The experimental results are interpreted in terms of the surface impedance tensor. It is assumed that the ribbon consists of an inner amorphous re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Recently, the off-diagonal magnetoimpedance in fieldannealed Co-based amorphous ribbons has been reported [4]. The asymmetric two-peak behavior of the field dependence of the off-diagonal impedance has been observed.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…Recently, the off-diagonal magnetoimpedance in fieldannealed Co-based amorphous ribbons has been reported [4]. The asymmetric two-peak behavior of the field dependence of the off-diagonal impedance has been observed.…”
mentioning
confidence: 97%
“…The coupling between the amorphous bulk and the crystalline layers results in the asymmetry in the GMI response. To explain the experimental data [4], it has been suggested that the surface layers have different thickness. In this work, we present the study of the influence of the crystalline layers on the off-diagonal magnetoimpedance in Co-based amorphous ribbons.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This effect is referred to as off-diagonal MI. Off--diagonal MI has been measured before in amorphous magnetic ribbons and wires [7,8]. * corresponding author; e-mail: grande@uniovi.es…”
Section: Introductionmentioning
confidence: 99%